Paying for health services in developing countries - "De Ferranti, David" (Washington, 1985)
This paper presents a overview of he principle issues, problems, and policy options in financing health services in developing countries. The shortcomings of existing policies, which finance health care to a significant extent from public revenue sources are reviewed. Alternative approaches are identified and examined with particular attention to.
Keywords: "Medical care, cost of - Developing countries"